Perceived recovery and stress states as predictors of depressive, burnout, and insomnia symptoms among adolescent elite athletes - Markus Gerber; Christin Lang; Serge Brand; Basil Gygax; Sebastian Ludyga; Caspar Müller; Sven Ramseyer; Sarah Jakowski (Hogrefe AG, 2023)
Abstract: Introduction: Finding ways to efficiently monitor the balance between recovery and stress is one of the most frequent requests from coaches and athletes and probably one of the best ways to prevent maladaptive psychological and physiological states. Therefore, the purpose of the present study was to monitor recovery-stress states of adolescent elite athletes across an entire school year using the 32-item Acute Recovery and Stress Scale (ARSS), and to examine the predictive value of recovery and stress states for depressive symptoms, burnout symptoms, and insomnia symptoms. Methods: Data are based on a 10-month longitudinal observational study. The sample consisted of 135 adolescent elite athletes (Mage=16.8 years) recruited from Swiss Olympic Partner Schools. The participants completed the ARSS 19 times (every second week), the Patient Health Questionnaire (PHQ-9), the Shirom-Melamed Burnout Measure (SMBM) and the Insomnia Severity Index (ISI) at baseline and follow-up. Results: Participants reported higher recovery than stress states across the entire school year. However, lower recovery and higher stress states significantly predicted mental health problems as indexed by depressive, burnout and insomnia symptoms. The predictive power of recovery and stress states was similar for depressive and burnout symptoms. For insomnia symptoms, only recovery state was a significant predictor. Conclusion: Our study highlights that a short psychometric instrument allows longitudinal monitoring of recovery-stress states. Coaches are encouraged to implement such an instrument to identify periods that are characterized by high stress and/or low recovery. Continuous monitoring may allow the timely implementation of prevention and intervention strategies in the training process.